Adherence of Candida albicans to Flexi-ble Denture Base Material - Zeina M Ahmad; Eman A Mustafa; Inas A Jawad (University of Mosul, College of Dentistry, 2012)
Assessment of Candida albicans adherence to flexible denture base material (Valplast) and con-ventional heat polymerized acrylic resin in the presence and absence of saliva. Materials and Me-thods: A total of 28 square specimens (10 mm x10 mm x3mm) were constructed from Valplast and acrylic denture base materials according to manufacturers' instructions and kept without finishing or polishing. C. albicans was isolated from patients with denture stomatitis. Fourteen specimens (7 of each material) were not coated with human saliva (control), deposited in yeast suspension (107 ) yeast cells/ml, incubated for 1hr at room temperature and washed with phosphate buffer saline and then stained with crystal violet. The remaining 14 specimens (7 of each material) were coated with saliva and treated as previously described. Adherent yeast cells in 84 fields of view (0.25mm2/field) of mate-rials were enumerated. The results were expressed as yeast cells/mm2 of material. Results: In compari-son between the two denture base materials, Candida adherence to acrylic resin (170 yeast cells/mm2) is greater than Valplast (126 yeast cells/mm2). Both saliva uncoated and coated acrylic samples have higher means of Candida adherence (208, 132 cells/mm2) than saliva uncoated and coated Valplast samples (175, 77 cells/mm2) respectively. High significant reduction in yeast counts was seen in both materials after saliva coating. Conclusions: Great reductions in yeast counts were determined in Val-plast material specially in saliva coated specimens when compared with acrylic resin.